Organización Contable en la Empresa MP Vehículos Sociedad Civil de la Ciudad de Loja, Periodo del 01 de Abril al 30 de Junio de 2023 - Maza Pacheco, Dayana Valeria (2024)
The present thesis work entitled, “ACCOUNTING ORGANIZATION IN THE COMPANY MP VEHICLES SOCIEDAD CIVIL OF THE CITY OF LOJA, PERIOD FROM APRIL 1 TO JUNE 30, 2023”, was developed with the purpose of organizing an accounting process that allows knowing the development of the company which is dedicated to the purchase and sale of new and used vehicles, with the purpose of the owner knowing the economic-financial situation within the analyzed period, it was carried out according to the proposed objectives, which helped to develop the accounting process to obtain the financial statements and finally with the application of indicators. The specific objectives set were met, the first objective is: Prepare the initial inventory adjusted to the needs and activities of the company MP VEHICULOS SOCIEDAD CIVIL which allows a control adjusted to the activities, proceeded by collecting supporting documents which allowed the information to be organized in order to carry out the initial inventory, the second objective is to develop the accounting process from the statement of financial position; statement of income; cash flow statement; cash flow statement; statement of changes in Equity; as well as explanatory notes, to know the financial and economic situation of the company MP VEHICULOS SOCIEDAD CIVIL, the financial statements that reflect the economic situation of the company were determined, with the purpose of serving as instruments of financial guidance for the manager of the company, which serve to summarize the information that will be presented in the annexes as support for the accounting practice, the third objective is to analyze the financial indicators that allow motorizing the financial statements of the company MP VEHICULOS SOCIEDAD CIVIL., to know the economic situation - financial that leads to correct decision making. With the results obtained after having completed the thesis work, it is established that through the accounting organization, it allows the manager to know the economic and financial reality of the company, which will help to make timely decisions, so it is recommended that the manager considers the accounting organization that allows the optimization of resources.